Automatic Call of CPO Toolpaths without Uncut Regions for 2.5 D Pocket Milling - Bahloul, Elhachemi; Guerraiche, Khelifa (Engineering, Technology & Applied Science Research, 2024)
In order to achieve the automatic call of any toolpath generation in 2.5 D pocket milling, new tool paths with offset parallel to the contour for any concave or convex polygonal shape are proposed in this article. Focus is given on several methods for addressing issues related to trajectory generation: the disappearance of edges when transitioning from one contour to another, the residual between passes, and the center of the pocket. A few selected test cases are presented for validation. The obtained results reveal that the approach introduced offers automatic toolpath generation for any polygonal shape and ensures efficient machining simulation without the appearance of material residues between passes in the corners or at the center of the pocket.